The presence of Airbnb offers high availability and local regulations for Airbnb - Falk, Martin (2023)
With the end of the pandemic city, tourism is coming back, and so also Airbnb. However, locals are increasingly concerned that Airbnb leads to a displacement of long-term tenants and rising rents (Duso et al., 2022). In a Referendum in Bern (Switzerland) in February 2022, the citizens voted for regulations against Airbnb. This paper investigates the determinants of high-availability listings in Swiss cities. Several definitions of high-availability listings are provided (booked for more than 90 or 180 days per year). In particular, we investigate whether the announcement of new regulations leads to a decline in the active status of high-availability offerings. The data is based on the total number of Airbnb listings in Swiss cities, with about 30,000 properties per month in the 20 major cities.